Factors Affecting Customer Continuance Intention using Online Food Delivery Service Post-COVID-19 in Malaysia - Saperi, Muhammad Ashif Mohd; Zaki, Nur Amalina Mohamad; Yaakop, Azizul Yadi; Sawitri, Dian Ratna; Zulkiffli, Siti Nur’`Atikah (International Review of Management and Marketing, 2026)
The use of online food delivery (OFD) services has remained high after the COVID-19 pandemic, prompting questions about the factors that influence consumer continuance intention. While most studies focused on intentions during the pandemic, fewer have examined customer continuance intention (CCI) in the post-pandemic context. This study investigates the effects of eight factors on CCI and the moderating role of technology experience. Using a quantitative design, data were collected from 462 Malaysian respondents with prior OFD experience through purposive sampling. Data were analysed via SPSS using descriptive statistics, multiple regression, and moderation analysis. Results show that familiarity is the strongest predictor of CCI, followed by perceived security, perceived usefulness, time-saving benefits, price-saving benefits, and perceived ease of use. Perceived privacy and food safety risk perception were not significant predictors of CCI. Moreover, technology experience did not moderate the relationships between the variables and CCI. Theoretically, this study contributes to the Technology Acceptance Model by identifying familiarity as a key post-adoption factor influencing continued use. Practically, the findings suggest that OFD providers should enhance user familiarity with their platforms to foster long-term customer usage.